Surgical Management of Osteochondritis Dissecans of the Glenoid via Autologous Bone Marrow Aspirate Concentrate and Extracellular Matrix Graft in an Eighteen-Year-Old College Pitcher - Mitchell T. Tingey BS; Mark A. Glover BS; Jeffery D. St. Jeor MD; Nicholas A. Trasolini MD; Benjamin S. Albertson MD; Anthony P. Fiegen MD; Brian R. Waterman MD (SAGE Publishing, 2024)
Background: Osteochondritis dissecans (OCD) affects the shoulder in only 0.6% of patients aged 2 to 19 years with disease most commonly in the humeral head. When the glenoid is affected, it is often in male overhead throwing athletes and treated with fixation via autologous osteochondral plugs following bone marrow aspirate. Indications: The primary indication for surgical management of OCD is failure of conservative management, often with imaging showing disruption of the glenoid subchondral plate. This patient is an 18-year-old male pitcher with over 2 years of chronic, deep-seated shoulder pain unresponsive to conservative management. Technique Description: We present a primary arthroscopic technique of autologous bone marrow aspirate concentrate graft for management of OCD in an 18-year-old college baseball pitcher. The patient was placed in the left lateral decubitus position with an axillary roll and standard portals were established. A loose fragmented flap with no underlying osseous material was debrided and a 3-cm central area of bony loss was identified. Bone marrow aspirate of 80 mL was taken from the anterior superior iliac crest. The aspirate was mixed with Biocartilage (Arthrex) to fill the defect flush with the surrounding tissue and sealed with fibrin glue. Ports were closed and an abduction sling was applied. Results: A recent review article demonstrated that athletes who underwent surgical management of OCD lesions returned to sports an average of 1.2 months sooner than those managed non-operatively, though this difference was not significant. This patient had a full return to play at 9 months. At 1-year follow-up, he made a full recovery and is currently playing professionally without shoulder pain. Discussion/Conclusion: Autologous bone marrow aspirate defect filling is a viable treatment of OCD, even in high-level overhead throwing athletes. It allows for arthroscopic treatment with long-term success in the treatment of pain and function. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.